AWARENESS AND ATTITUDE REGARDING PAIN MANAGEMENT AMONG NURSES WORKING IN MAJOR HOSPITAL DEPARTMENTS - AHMED, S; BANO, I; SHAFQAT, R (Biological and Clinical Sciences Research Journal, 2024)
Pain management is a critical aspect of nursing care, yet the awareness and attitudes of nurses regarding this issue remain understudied, particularly in the context of Pakistan. Objective: This study evaluated nurses' understanding and attitudes regarding pain management in central hospital departments. Methods: A descriptive cross-sectional study was conducted at Nishtar Hospital, Multan, Pakistan, from March 2023 to March 2024. Using convenient sampling, 300 nurses from various hospital departments were included, including internal medicine, paediatrics, outpatient, surgical unit, ICU, and emergency. A 25-item questionnaire comprising polar and Likert scale questions was utilised to assess knowledge and attitudes. Descriptive statistics were employed to analyse the data, and mean scores were compared using appropriate statistical methods. Results: Of the participants, 67.3% (95% CI: 61.4%, 70.9%) demonstrated good knowledge about pain management, with a mean score of 7.07 ± 1.66. Furthermore, 50.6% (95% CI: 45.7%, 55.3%) exhibited a positive attitude, with a mean score of 48.2 ± 6.08. While no significant difference in mean knowledge scores was observed between genders (p = 0.754), a statistically significant difference was found in mean attitude scores (men: 49.03, women: 47.22, p = 0.01). Conclusion: Despite possessing good knowledge, nurses in Pakistan display a comparatively less favourable attitude toward pain management, highlighting the need for targeted interventions to address attitude-related barriers.